Using Cubing Strategy in Teaching Explanation Text for Eleventh Grade Students of Senior High School - Ayu Putri Nulmi; Yetty Zainil (Universitas Negeri Padang, 2018)
This paper discusses how to use Cubing Strategy in teaching Explanation text at Senior High School. Based on the writers’ experience in teaching English, many students find difficulties in writing explanation text. Considering this problem, the teacher needs to apply a strategy in teaching and learning process to help the students understand the text. Cubing Strategy is a creative, hands-on activity which develops critical thinking and promotes deeper understanding and in-depth exploration of a topic. It uses a cube-shaped graphic organizer to prompt students to look at a topic from many different angles and levels. On each side of a cube, the student writes answers to prompts or questions. By applying the Cubing Strategy in writing an explanation text, the students may create a better explanation text.